Pelatihan Pembacaan Puisi Siswa Kelas VIII SMP Negeri 2 Dumai Timur - Jamilin Tinambunan; Rizki Rizki; Hermaliza Hermaliza; Rijali Abdillah Zikhri; Adristi Afdal (UIR Press, 2022)
Poetry reading training is very important for junior high school students. In addition to practicing literary skills, reading poetry can also train students' mental abilities to appear in front of many people. Reading poetry is one of the teaching literature in the junior high school curriculum. As a literary work, poetry has many benefits for children's development, namely for junior high school students. Reading poetry will shape the character of children to be wiser and mature. In poetry, you will find various kinds of emotions, stories, moral messages and much more. In addition, reading poetry can also build students' character and personality because poetry contains many messages and moral values, therefore this community service needs to be done by formulating the problem of how to increase knowledge and poetry reading skills through training that will be carried out Class VIII students of SMP Negeri 2 Dumai Timur. This is in accordance with the purpose of knowing and describing the knowledge and poetry reading skills of Class VIII students of SMP Negeri 2 Dumai Timur. This dedication method uses a descriptive method. The output target of this service activity is to improve knowledge, skills, and experience in reading poetry for Class VIII students of SMP Negeri 2 Dumai Timur and the Sajak journal will be published.